Upscaling and Outsclaing of Rabi Castor in Andhra Pradesh- Opportunities and Limitations - Ramanjaneyulu, A. V.; Reddy, K. Dharma; Reddy, A. Vishnuvardhan; Kumar, M. V. Nagesh; Ahammed, S. Khayum; Gouri Shankar, V.; Neelima, T. L. (International Journal of Bio-resource and Stress Management, 2014)
Castor has been a traditional oilseed crop grown under rainfed conditions in an area of 0.35 m ha in Andhra Pradesh. However, these days, most of the dry land farmers in Andhra Pradesh are shifting from castor to Bt cotton and maize during kharif season because of less yield and remunerative returns from castor. It was mainly due to drought, botrytis disease, poor adoption of agronomic and plant protection measures besides non-availability of good quality seeds of castor. As castor is an important industrial oilseed crop fetching more than ` 2500 crores of foreign exchange, researchers felt that it is essential to increase the productivity of castor by promoting its’ cultivation in rabi season as crop will be free from botrytis grey rot disease and crop can be grown with less water. The research and on-farm demonstrations carried out in Andhra Pradesh proved that, rabi castor is more remunerative than kharif castor and rabi groundnut. This paper describes the agrotechniques developed at research station level and the way rabi castor was promoted among the farmers in Andhra Pradesh through upscaling and outscaling extension strategy.